Assessing the Quality of Education: A Theoretical Review of Quality Improvement Techniques and Approaches - Tamlekha, Tamlekha; Hariyanto, Teguh; Ropi Fahmi, Dede; Nurjaman, Irman; Samsul Arifin, Bambang (Teunuleh Publisher, 2025)
The quality of education is a strategic issue that continues to be a concern in the development of the education system, both at the policy level and institutional practice. However, efforts to improve the quality of education are often dominated by technocratic approaches that tend to reduce quality to mere administrative and quantitative indicators. This article aims to examine the concept of educational quality theoretically and examine approaches and techniques for improving the quality of education as stated in the scientific literature. This study uses a qualitative approach with a literature study method, by analyzing relevant textbooks, journal articles, and policy documents. The results of the study show that quality education is a multidimensional concept that includes outcomes, learning processes, and the education system as a whole, and is influenced by social and institutional contexts. Various approaches to quality improvement, such as managerial, systemic, school-based, and quality culture approaches, have different characteristics and focuses, so they cannot be applied uniformly. Quality improvement techniques, such as continuous planning and evaluation, academic supervision, curriculum development, and data utilization, need to be integrated consistently with the approach used. This article emphasizes the importance of theoretical and contextual understanding in efforts to improve the quality of education as a sustainable process.